Foresight of the agroindustrial engineering to 2035 - Application of the delphi method as a dynamizer of curricular changes [Prospectiva de la ingeniería agroindustrial a 2035 - Aplicación del método Delphi como dinamizador de cambios curriculares] (2019)
The purpose of this article is to present the results of the application of the first Delphi round for Faculties of Agroindustrial Engineering in the framework of a prospective project, the objective was to establish research priorities, technology and areas of curricular interest for Faculties of Agroindustrial Engineering and related to the year 2035, for this purpose a survey was conducted to more than 200 national and international stakeholders related to Agroindustrial Engineering, which contained 293 variables related to the core aspects of agro-industry, that is, management, production, transformation and marketing as well as four complementary thematic groups: CIT's, sustainability, agroindustrial residues and biotechnology. On this questionnaire responses were obtained in Likert scale, which were treated through the calculation of the mode, modal frequency and percentage of consensus, among the most important results the participation of 53 experts from countries such as Spain, Peru, Mexico, Chile and Argentina, from Universities, companies and public institutions is highlighted, some of the technologies with the highest percentage of consensus were, big data, Internet of Things (digital interconnection of daily objects), sustainable agriculture, sustainable constructions, Genetically Modified Organisms, biofuels, carbon capture, use and storage (CCUS), Collaborative Learning in Virtual Worlds (Second Life), Innovation Capabilities, among others. It was observed the existence of new topics and technologies that can be taken into account for the restructuring of the curriculum of the Faculties of Agroindustrial Engineering, as well as for the prioritization of topics, technologies and innovations in terms of training experiences or training courses, extension programs, new lines of research and creation of new graduate programs. © 2019 Latin American and Caribbean Consortium of Engineering Institutions. All rights reserved.